Health Care Access Among U.S. Adults Who Drink Alcohol Excessively: Missed Opportunities for Prevention - Machell Town, MS; Timothy S. Naimi, MD, MPH; Ali H. Mokdad, PhD; Robert D. Brewer, MD, MSPH (Centers for Disease Control and Prevention, 2006)
Introduction Excessive alcohol consumption kills approximately 75,000 people annually in the United States. Although alcohol screening among primary care patients is recommended by the U.S. Preventive Services Task Force, it is rarely performed. It is unclear whether low screening rates are due to limited access to health care, missed screening opportunities during patient visits, or both. Methods Data came from the 2002 Behavioral Risk Factor Surveillance System, a population-based telephone survey of noninstitutionalized U.S. adults. Current health insurance status and a history of a recent medical checkup (within 2 years) were assessed in relation to alcohol consumption status. Excessive drinkers included those who reported binge drinking (consuming five or more drinks on one or more occasions in the past month), heavy drinking (consuming more than 60 drinks in the past month for men or more than 30 for women), or both. Results The prevalence of excessive drinking among the general population (17%) was only slightly higher than the prevalence among those with current health insurance (15%) or a recent checkup (14%). Among excessive drinkers, 79% had current health insurance and 78% had a recent checkup. Although excessive drinkers were somewhat less likely to have health insurance or a recent checkup compared with nonexcessive drinkers and nondrinkers, these differences were less pronounced after stratifying by age. Excessive drinkers with the lowest rates of health insurance were young, Hispanic, less educated, and unemployed. However, most excessive drinkers who lacked insurance or a checkup were employed. Conclusion Most excessive drinkers were insured and had a recent medical checkup, suggesting that low screening rates among excessive drinkers are mostly due to missed screening opportunities rather than a lack of screening opportunities. Systems approaches to address these missed opportunities should be aggressively implemented.